The Seasonality of Mesoscale Eddy Intensity in the Southeastern Tropical Indian Ocean - Zu, Yongcan; Fang, Yue; Sun, Shuangwen; Yang, Guang; Gao, Libao; Duan, Yongliang (Frontiers in Marine Science, 2022)
The seasonality of mesoscale eddy intensity in the southeastern tropical Indian Ocean (SETIO) is investigated using the latest eddy dataset and marine hydrological reanalysis data. The results show that the eddy intensity in an area to the southwest coast of the Java Island has prominent seasonality - eddies in this area are relatively weak during the first half of year but tends to enhance in August and peaks in October. Further analysis reveals that the strong eddies in October are actually developed from the ones mainly formed in July to September, and the barotropic instability and baroclinic instability are the key dynamics for eddy development, but each plays a different role at different development stages. The barotropic instability plays an important role in the early stage of eddy development, while in the late development stage the baroclinic instability becomes the major energy contributor of eddy development.